Влияние одноосного упругого сжатия на условия возбуждения и параметры рекомбинационных волн в компенсированном кремнии - Зикриллаев, Н.Ф; Сатторов, А.А; Норкулов, Н; Абдуллаева, Н.У; Ибрагимова, Б.С (SCIENCE and SOCIETY, 2024)
For the study, silicon samples were obtained, diffusion doped with impurity manganese atoms with crystal orientation ˂111˃ and ˂110˃ with different resistivity of p-type conductivity. From an analysis of the research results, it was established that uniaxi- al elastic compression greatly changes the amplitude and frequency of recombination waves. The physical mechanism for changing the parameters of self-oscillations of current is explained by the model of the band diagram of an inhomogeneous semiconductor material, which is formed due to the charge state of impurity manganese atoms in compensated silicon.
Keywords: silicon; diffusion; manganese; amplitude; frequency; uniaxial compression; pressure coefficient; electron; hole